RAISING COMMUNITY AWARENESS OF HALAL PRODUCT CONSUMPTION AND HALAL LIFESTYLE: A TRIPLE HELIX MODEL - Dien Mardhiyah; Imron Mawardi; Tika Widiastuti; Muhammad Ubaidillah Al Mustofa; Syahidah Abdullah; Rizky Amalia Sinulingga; Errin Dwi Saptowati (Universitas Airlangga, 2023)
This study formulates a triple helix model for increasing community awareness of halal product consumption and lifestyle. It is essential to increase halal awareness not only as a form of religious obedience but also to provide consumers protection, improve product quality, encourage product innovation, and fulfil international standards. This qualitative study constructs a Triple Helix model using a descriptive analysis technique and the Inputs, Activities, Outputs, Outcomes, and Impact (IAOOI) Approach. The findings indicate that the government is crucial in answering the research question. The government is expected to provide optimal support for creating such an environment through laws, regulations, infrastructure development, and other methods. Academicians are responsible for conducting scientific research in the halal industry and social programs and disseminating their findings to the general public. Practitioners in the halal industry can participate in community-based events to increase public awareness of halal products and lifestyles. This research contributes to developing relevant policies for related stakeholders to increase community awareness of halal product consumption and lifestyle.